Towards a political concept of dignity - Samuel Harrison (Political Research Exchange)
This paper proposes a new way of thinking about the concept of dignity. It argues that existing conceptions of dignity in moral and legal philosophy fail to meet three key tests: conceptual soundness, analytical usefulness, and a capacity to vindicate the principle of moral egalitarianism. It suggests that we can better satisfy all three of these conditions if we treat dignity as a relational and political concept that is defined by a sense of what we are due. This means its content derives not from any transcendental truth or legal authority but has to be negotiated between different actors. It can then be asserted as part of an egalitarian project without needing to make reference to an external authority or a confused conceptual base. It seeks to show that this understanding of dignity is free of the conceptual confusion that plagues the existing conceptions; is closer to the ‘common’ understanding of dignity in ordinary language and thus more analytically useful; finally can be deployed more successfully in defence of the principle of moral equality.